Common shared system model for evolvable assembly systems - Sanderson, David; Chaplin, Jack; Ratchev, Svetan (2018)
A vital aspect of distributed control in an adaptable production system is coherence between each system resource. The Evolvable Assembly Systems project addresses this challenge using a common shared system model. This paper provides an overview of the project and the shared system model approach as implemented in a real world demonstration cell.